Epidemiology of cerebral palsy in England and Scotland, 1984–9. Issue 1 (1st July 1998) - Pharoah, P O D; Cooke, T; Johnson, M A; King, R; Mutch, L
Abstract : AIMS: To report on the epidemiology of cerebral palsy in England and Scotland, to provide information on the prevalence of cerebral palsy and the severity of the disability or any co-morbidity. METHODS: Cerebral palsy registers were compiled from multiple sources of ascertainment covering all of Scotland and the counties of Merseyside, Cheshire, Berkshire, Buckinghamshire, Northamptonshire and Oxfordshire in England. All cases of cerebral palsy born in 1984 to 1989, to mothers resident in the area, were included. Denominator number of live births and neonatal deaths for determining birthweight specific prevalence were obtained from birth and death registrations. Learning, manual, and ambulatory disabilities were graded for severity. Any co-existing sensory (hearing or visual) morbidity was also graded for severity. RESULTS: There were 789 411 live births in 1984–9, with 3651 neonatal deaths (neonatal mortality 4.6 per 1000 live births) and 1649 cases of cerebral palsy—a cerebral palsy prevalence of 2.1 per 1000 neonatal survivors. The birthweight specific cerebral palsy prevalence ranged from 1.1 per 1000 neonatal survivors in infants weighing ⩾2500 g to 78.1 in infants weighing <1000 g. There was no significant time trend in prevalence of cerebral palsy in any of the birthweight groups, in contrast to the fall in neonatal mortality observed in all birthweight groups. Of the 1649 cases of cerebral palsy, 550 (33.4%) had severe ambulatory disability (no independent walking), 390 (23.7%) had severe manual disability (incapable of feeding or dressing unaided), 381 (23.1%) had severe learning disability (IQ <50), 146 (8.9%) had severe visual disability (vision <6/60 in the better eye) and 12 had severe hearing disability (>70 dB loss). CONCLUSIONS: Registers fill an important gap left by the lack of routine data on the prevalence of disability in children. The ability to record trends in the prevalence and the severity of the disability should inform those who have responsibility for providing services for children with disabilities.